Money does not buy happiness… or does it? An investigation of the relationship between individual income and life satisfaction in the national income dynamics study - Gaya, Lerato (Organisational Psychology, 2021)
On 1 January 2019, South Africa introduced a national minimum wage of R20 per hour. Minimum wages have been said to merely satisfy basic needs and not allow individuals to thrive; thus, not allowing for a decent life. Past research has argued for the importance of living wages, which are defined as a wage level that allows an individual's life satisfaction (or quality of life) to move from negative to positive. Studies exploring the relationship between individual income and life satisfaction have typically assumed a linear relationship between the two variables. However, there is evidence that the relationship may be more complex, following the discovery of non-linear relations (e.g. an S-shaped curve). The purpose of this dissertation was to explore the nature of the relationship between income and life satisfaction in the National Income Dynamics Study (NIDS), a South African household panel study which gathers various wellbeing related information from a nationally representative sample of citizens. This was done by exploring three research objectives. The first was to assess the nature of the relationship between individual income and life satisfaction. The second was to determine an approximate living wage amount based on individuals' subjective experiences; and the third to determine the longitudinal relationship between income and life satisfaction. For this dissertation, data collected in 2008 (wave 1), 2010 (wave 2), 2012 (wave 3) and 2014 (wave 4) was used to determine the short- and long-term relationship between individual income and life satisfaction. This study did not find the expected S-shaped relationship, nor any other shape of relationship; however, the variance in life satisfaction decreased at greater income levels: There were individuals who were highly satisfied with their lives at each income level, but no individuals were extremely dissatisfied with life from a certain income level onward. Thus, severe life dissatisfaction disappears with higher income, but higher income does not lead to higher life satisfaction. A repeated measures design was utilised to ascertain the longitudinal relationship between income and life satisfaction. No clear systematic pattern emerged in the relationship between income and life satisfaction over time, thus supporting Easterlin's Happiness-Income paradox, which suggests no association between income and life satisfaction over longer periods of time. The dissertation concludes by providing recommendations, limitations and implications of the results for research and practice. For example, the dissertation suggests that policy makers should consider and continue discussions on implementing wage thresholds above the national MW.